Feasibility Analysis of Magnetorheological Absorber in Recoil Systems: Fixed and Field Artillery - Ouyang, Qing; Hu, Hongsheng; Zhao, Wei; Wang, Jiong; Li, Zhaochun (Frontiers in Materials, 2020)
Magnetorheological (MR) absorbers in the artillery recoil systems are usually used to dissipate the impact energy as much as possible and reduce the recoil force transmitted to the artillery carriage, while the firing stability of artillery during buffer process is rarely considered. In this paper, we analyzed the firing stability characteristics of the fixed artillery and the field artillery systems and established corresponding mechanical models. Then, we proposed the ideal recoil F-v curves of these two kinds of artillery respectively. The “platform effect” of recoil curve was taken as the recoil force control target of the fixed artillery, while based on the firing stability, the linear segmented recoil curve was drawn up as the ideal recoil buffer control target of the field artillery. To verify the feasibility and controllability of the designed multi-stage MR absorber in two kinds of recoil buffer system, the impact tests were conducted under different current loadings. The test results show that the designed MR absorber can realize different buffer control effects by changing the input current, but the ideal “platform effect” recoil curve of the fixed artillery cannot be completely realized due to small controllable damping force output. In the field artillery recoil system, the MR absorber can realize ideal recoil buffer control in the range of 0 to 25 degree firing angles.